Stunted Mangrove Trees in the Oligotrophic Central Red Sea Relate to Nitrogen Limitation - Anton, Andrea; Almahasheer, Hanan; Delgado, Antonio; Garcias-Bonet, Neus; Carrillo-de-Albornoz, Paloma; Marbà, Núria; Hendriks, Iris Eline; Krause-Jensen, Dorte; Saderne, Vincent; Baldry, Kimberlee; Duarte, Carlos M. (Frontiers in Marine Science, 2020)
Mangroves are important coastal ecosystems of warm climatic regions that often grow in shallow saline or brackish waters of estuaries and river mouths affected by wide tidal intervals and receive abundant nutrient supply. However, mangroves also occur in areas of little tidal influence and devoid of riverine inputs, where they can develop a stunted plant form. Here we report that Avicennia marina trees in the fringe of the Red Sea have maximum heights toward the lower range of that reported elsewhere (average maximum canopy height of 4.95 m), especially in the central region, where mangroves are stunted with an average tree height of 2.7 m. Maximum tree height and chlorophyll a concentration correlated positively with nitrogen concentration in the leaves of A. marina. We conclude that the stunted nature of mangrove trees in the central Red Sea is likely driven by nitrogen limitation.